Traumatic dental injuries in relation to quality of life among school children in Baghdad /Iraq - Jamal , Shahad; MH Radhi, Nada J (Journal of Baghdad College of Dentistry, 2021)
Background: One of the significant public health problems is the traumatic dental injury to the anterior teeth, it has a great impact on children’s daily. Physical and psychological disturbance, pain and other negative impacts, such as tendency to avoid laughing or smiling may be associated with traumatic dental injuries, that may affect the social relationships. To determine the occurrence of traumatic dental injuries in relation to quality of life, this study was established among children of primary schools. Material and Methods: A cross-sectional study was conducted among private (574) and governmental (1026) primary school children in Baghdad city. Dental trauma was assessed according to Ellis and Davey classification in1970 and quality of life concerning a child Perceptions Questionnaire (CPQ) was used which consisted according to Jokovic et al.in 2006. Statistical analysis was done using IBMSPASS version (21). Results: Among the permanent anterior dentitions; the most widespread injured teeth were the maxillary central incisors. The boys were more affected with traumatic teeth than girls, as well as a higher percentage noticed in governmental schools than in private schools. Among all quality of life questionnaire, a higher percentage were observed in boys rather than in girls, as well as in governmental schools a higher percentage were listed more than in private schools, all differences were statistically highly significant. Conclusion: A higher association was noticed between traumatic anterior teeth and quality of life for children. Keywords Traumatic dental injuries, quality of life and oral condition.